The Relationship of Adolescent and Parent Preferences for Treatment Modality With Satisfaction, Attrition, Adherence, and Efficacy: The Coping With Head Injury Through Problem-Solving (CHIPS) Study. (19th November 2018) - Wade, Shari L; Cassedy, Amy E; Sklut, McKenna; Taylor, H Gerry; McNally, Kelly A; Kirkwood, Michael W; Stancin, Terry; Kurowski, Brad G
Abstract: Objective: To characterize treatment preferences for delivery of family problem-solving treatment (F-PST) to adolescents with behavioral challenges following traumatic brain injury (TBI) and to examine associations with attrition, adherence, satisfaction, and efficacy. Method: Adolescents who had been hospitalized for moderate to severe TBI were randomized to face-to-face F-PST ( n = 34), therapist-guided online F-PST ( n = 56), and self-guided online F-PST ( n = 60). Adolescents and parents rated treatment convenience and anticipated benefit before group assignment. Sessions completed served as an index of adherence. Satisfaction was rated posttreatment. The Behavior Rating Inventory of Executive Function and Strengths and Difficulties Questionnaire were used to assess parent-reported behavioral concerns. Results: Both parents and adolescents were more likely to agree or strongly agree that they anticipated self-guided online F-PST to be the most convenient relative to either of the therapist-involved approaches. Parents were also less likely to anticipate face-to-face treatment as most beneficial, relative to the two online treatments. Adolescent preferences were significantly related to attrition with 27% versus 13% dropout rates for those assigned to nonpreferred and preferred treatments, respectively. Parent and adolescent preferences before treatment were unrelated to post-intervention satisfaction, adherence, or improvements in parent-reported child behavior problems. Conclusions: Online treatments are perceived favorably among adolescents with TBI and their parents. For adolescents, these pretreatment preferences influenced treatment completion. Poor correspondence between initial preferences and posttreatment satisfaction and benefit suggests that therapeutic experience more strongly influences ultimate satisfaction.